Diagnostic and prognostic significance of cyclin A expression in low-grade astrocytomas: comparison with astrogliosis and high-grade tumours. Issue 3 (21st December 2007) - Hara, A; Saegusa, M; Ichinoe, M; Okayasu, I
Abstract : Aim: Definitive distinction between low-grade astrocytoma and astrogliosis is a long-standing difficulty due to their similar histopathological characteristics. To clarify differences in biological significance, this study focused on various components of the cell cycle machinery and proliferation as key parameters, comparing expression in astrogliosis, as well as low- and high-grade astrocytomas. Methods: The expression of p16, p21 and p27, and cyclin A, cyclin D1, cyclin E, Rb and Ki-67 was immunohistochemically examined in 40 cases of astrogliosis and 48 cases of low-grade astrocytomas (grade II), as well as 50 high-grade tumours (grades III and IV). The results were also compared with survival data for the astrocytomas. Results: Cell proliferation determined by Ki-67 immunoreactivity did not differ between astrogliosis and low-grade tumours. Average labelling indices (LIs) for p16, p21, Rb, cyclin A and cyclin E showed a stepwise increase from astrogliosis, through low- to high-grade astrocytomas, indicating the possibility that over 9%, 6% and 4% of LIs for p16, p21 and cyclin A, respectively, may be useful predictors in the case of the latter, in contrast to significant decrease in p27 LIs. Significantly higher mean LI values for cyclin D1 were also evident in astrogliosis (12.42) as compared with astrocytomas (low grade, 2.26; high grade, 4.60). Positive correlations between LIs for Rb and Ki-67 were observed with astrogliosis and low- but not high-grade tumours. In addition, high cyclin A LI values were independently associated with poor outcome in low-grade tumours. Conclusion: These findings provide evidence that expression of cell-cycle-related molecules may be a reliable parameter for differential diagnosis of low-grade astrocytomas and astrogliosis. Moreover, detection of cyclin A appears to be useful for predicting behaviour of low-grade astrocytomas.